Keeping two balls in the air: The bleisure travel experience - Bardia Batala; Lisa Slevitch (Annals of Tourism Research Empirical Insights, 2024)
This study examines bleisure travel across pre-trip, during, and post-trip phases. After interviewing 23 bleisure travelers, the study found that in the pre-travel phase, bleisure travelers had more complex planning and needed more coordination. Therefore, they were well-organized, futuristic, and competent in travel arrangements. During the travel, they sought 'educational experiences', 'short-squeezed leisure plans', 'family and kids-oriented activities', and preferred 'not trying one-time events'. They used strategies such as 'flexibility in travel arrangement', 'clarification of travel companions', 'mixing business and leisure activity', and 'remote work' to balance the two travel purposes. Finally, in the post-trip phase, bleisure travelers described feeling 'physically tired but mentally rejuvenated' with a sense of being 'free of the guilt' of their absence from home.
Keywords: 330; Bleisure travel; Tourist experience; Business travel; Leisure travel; Hybrid travel